EFL TERTIARY STUDENTS’ CHALLENGES AND COPING STRATEGIES ON DUOLINGO ENGLISH PRACTICE TEST : A REFLECTION JOURNAL - Nirmala Nirmala; Maulina Maulina; Tri Indah Rusli (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examined the challenges faced by college-level EFL students in taking the Duolingo English Practice Test and the strategies they used to overcome them. The study utilised the journal reflection method, where participants recorded their experiences while taking the test. Data were analysed qualitatively to identify patterns of difficulty and adjustment mechanisms used. The results showed that students faced challenges in listening comprehension, time management, and psychological pressure during the test. To overcome them, they applied various strategies, such as intensive practice, the use of additional applications, and stress management techniques. These findings highlight the importance of developing self-directed learning strategies for EFL students in the face of digital-based exams. In conclusion, although the Duolingo English Practice Test presents challenges for EFL students, effective adaptation strategies can help them improve their performance. This study recommends the integration of technology-based training in the curriculum to improve students' preparedness for online exams.